2009
DOI: 10.1099/mic.0.025643-0
|View full text |Cite
|
Sign up to set email alerts
|

Subinhibitory concentrations of the cationic antimicrobial peptide colistin induce the pseudomonas quinolone signal in Pseudomonas aeruginosa

Abstract: Colistin is an important cationic antimicrobial peptide (CAMP) in the fight against Pseudomonas aeruginosa infection in cystic fibrosis (CF) lungs. The effects of subinhibitory concentrations of colistin on gene expression in P. aeruginosa were investigated by transcriptome and functional genomic approaches. Analysis revealed altered expression of 30 genes representing a variety of pathways associated with virulence and bacterial colonization in chronic infection. These included response to osmotic stress, mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 67 publications
4
59
2
Order By: Relevance
“…Although cells exposed to carbenicillin exhibit a dramatic morphology change, we found that exposure to tobramycin, but not carbenicillin, resulted in profile shifts of both PQS and AQNO families during swarming. This is in contrast to reports that have suggested a general PQS response to antimicrobials (22,26,27). Our findings are consistent with the hypothesis that AQ modulations following tobramycin exposure during pre-biofilm swarming should contribute to antibiotic tolerance (22,25,38), however, other factors must control P. aeruginosa tolerance to carbenicillin.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Although cells exposed to carbenicillin exhibit a dramatic morphology change, we found that exposure to tobramycin, but not carbenicillin, resulted in profile shifts of both PQS and AQNO families during swarming. This is in contrast to reports that have suggested a general PQS response to antimicrobials (22,26,27). Our findings are consistent with the hypothesis that AQ modulations following tobramycin exposure during pre-biofilm swarming should contribute to antibiotic tolerance (22,25,38), however, other factors must control P. aeruginosa tolerance to carbenicillin.…”
Section: Discussioncontrasting
confidence: 57%
“…Because previous reports have shown various roles for PQS, namely as a stress response, for planktonic P. aeruginosa cells exposed to antimicrobials (22,26,(38)(39)(40), we were interested to explore how AQs mediate P. aeruginosa behavior in motile, prebiofilm swarm communities. Additionally, the CRM chemical profile of P. aeruginosa swarms provided evidence that tobramycin exposure cues aspects of PQS production or regulation that carbenicillin does not (Fig.…”
Section: Pqs Promotes Cell Death and Reduced Swarming For Cells Exposmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, at subinhibitory concentrations, many antibiotics appear to influence the expression of virulence factor genes, such as those for phenazine biosynthesis and regulation in pseudomonads (Cummins et al, 2009;Liang et al, 2008;Linares et al, 2006;Mitova et al, 2008;Shen et al, 2008;Skindersoe et al, 2008). The observations indicate that the effects of antibiotics may vary depending on the target bacterial species and the kind of antibiotic (Fajardo & Martinez, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…So far, an interpretation was only suggested for the effect of subinhibitory antibiotic concentrations on the triggering of virulence factor expression. Sensing such foreign toxic molecules would allow pseudomonas species to obtain increased fitness in a competitive environment (Cummins et al, 2009;Shen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%